Determining the role of nasolaryngoscopy in the initial evaluation for upper airway injury in patients with facial burns. Issue 3 (May 2018) - Freno, Daniel; Sahawneh, James; Harrison, Sarah; Sahawneh, Tim; Patterson, Scott; Kahn, Steven A.
Highlights: Routine fiberoptic nasolaryngoscopy is not useful in assessing for airway injury. A thorough history and physical remains the best screening tool for airway injury. Dyspnea, tachypnea and hypoxia are the most predictive of significant injury. Nasolaryngoscopy may be helpful in a subset of symptomatic patients. Abstract: Background: Upper airway injuries can be fatal in burn patients if not recognized, a scenario that causes a significant amount of anxiety for physicians providing initial assessment of burn patients. Early elective intubation is often performed; sometimes unnecessarily. However, some providers employ nasolaryngoscopy for patients presenting with facial burns or signs/symptoms of upper airway injury in order to assess the need for intubation, but this practice is not considered standard of care and may also be unnecessary. Evidence is currently lacking about the utility of nasolaryngoscopy as an adjuvant assessment during evaluation of potential upper airway burn injuries. The objective of this study was to determine if nasolaryngoscopy provides additional information to the history and physical in making the decision to electively intubate patients with facial burns. Methods: This study was a retrospective analysis of all patients who underwent fiberoptic nasolaryngoscopy after facial burn injury to evaluate for upper airway injury associated with burns over a 2 year period at a regional burn center. During this time period, all patients who presented with facial burns, soot, or carbonaceous sputum underwent nasolaryngoscopy to look for upper airway injury regardless of mechanism of injury. Patients intubated prior to arrival were excluded from the study. Patients were considered to have signs/symptoms of airway injury (symptomatic) if they presented with dyspnea, tachypnea, hypoxia, or significant burns to buccal mucosa. Procedure notes were used to determine if supraglottic/glottic injury (erythema or edema) was present on nasolaryngoscopy. Presence of pathologic changes and whether they led to intubation were evaluated in the asymptomatic and the symptomatic groups of patients. Select individual records were inspected further to help determine if the nasolaryngoscopy findings altered management plans and if intubation was ultimately necessary based upon the presence or absence of a cuff leak and the duration of intubation. Results: Twenty-two patients were symptomatic upon presentation, 14 of which had positive findings on laryngoscopy and 7 (50%) were intubated. One-hundred and eighty-eight patients were asymptomatic, 58 (31%) of which had either erythema or edema or carbonaceous debris on nasolaryngoscopy, and only 2 (1%) were intubated. These patients were both extubated within two days. None of the 130 asymptomatic patients with negative nasolaryngoscopy were intubated. Conclusions: This study showed disparity between signs and symptoms of airway injury and nasolaryngoscopy findings. Asymptomatic patients showed pathologic changes in 30% of scopes, but this finding only changed management 1% of the time. Furthermore, the two patients in this group were extubated quickly, suggesting they may have been suitable for observation without intubation. These results indicate that the presence of erythema or edema is of questionable clinical significance in asymptomatic patients and nasolaryngoscopy is of limited benefit in this group. Only 50% of the symptomatic patients with airway injury evident on nasolaryngoscopy were actually intubated, also bringing into question the significance of the pathologic changes in this group. However, negative nasolaryngoscopy may have had some benefit in preventing intubation in a few, select symptomatic patients. This study suggests that a thorough history and physical is the best tool to identify patients at higher risk of upper airway injury who need intubation, but this should be further studied in prospective trials to determine the definitive role of nasolaryngoscopy.